2015
DOI: 10.1016/j.envres.2014.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic exposure, telomere length, and expression of telomere-related genes among Bangladeshi individuals

Abstract: Background Inorganic arsenic is a carcinogen whose mode of action may involve telomere dysfunction. Recent epidemiological studies suggest that chronic arsenic exposure is associated with longer telomeres and altered expression of telomere-related genes in peripheral blood. In this study, we evaluated the association of urinary arsenic concentration with expression of telomere-related genes and telomere length in Bangladeshi individuals with a wide range of arsenic exposure through naturally contaminated drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 69 publications
6
25
2
Order By: Relevance
“…In human atherosclerosis telomerase is activated and TERT expression correlates with the extent of the disease; however, the mechanisms underlying telomerase activation and the physiological role of inducible TERT expression in atherosclerosis remain to be discovered. 11,12 In correlation with these findings, this study suggests the association of increased hTERT expression with the increased risk of coronary artery diseases.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In human atherosclerosis telomerase is activated and TERT expression correlates with the extent of the disease; however, the mechanisms underlying telomerase activation and the physiological role of inducible TERT expression in atherosclerosis remain to be discovered. 11,12 In correlation with these findings, this study suggests the association of increased hTERT expression with the increased risk of coronary artery diseases.…”
Section: Discussionsupporting
confidence: 77%
“…The association of telomere with atherosclerosis and CVD has been supported by a large number of studies. 5,11,12 Decreased hTERT mRNA expression and shorter telomere was found associated with atherosclerosis in various studies. 7,[24][25][26] In this study, among 50 study subjects, 31 patients were diagnosed with coronary artery diseases and the patients with CAD showed 4 fold higher hTERT mRNA expression than non-CAD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, accumulating evidence indicates that leukocyte telomeric DNA may be one important target of environmental pollutants [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies with arsenic, a common constituent of pesticides, showed increased telomerase activity and longer telomeres at low doses, but the opposite at higher doses [Li et al, ]. In support of these findings, Gao et al [] showed an increase in telomere length in individuals exposed to very high doses of arsenic in drinking water.…”
Section: Discussionmentioning
confidence: 93%